The World Health Organization and its international responsibility in facing epidemics - الجنابي, هديل صالح; نجم, أسامة يوسف (Journal of Legal Sciences, 2021)
The spread of COVID-19 virus over the world had affected all aspects of life on the earth. This had led to investigating the role of the specialized international organizations like the World Health Organization (WHO) , specially after the criticisms for its performance during this pandemic.This study tries to explore the principles upon which the WHO responsibility was proposed and whether the criticisms and accusations for it are true.